2023
DOI: 10.3892/br.2023.1601
|View full text |Cite
|
Sign up to set email alerts
|

(−)‑Epigallocatechin‑3‑O‑gallate upregulates the expression levels of miR‑6757‑3p, a suppressor of fibrosis‑related gene expression, in extracellular vesicles derived from human umbilical vein endothelial cells

Abstract: As pulmonary fibrosis (PF), a severe interstitial pulmonary disease, has such a poor prognosis, the development of prevention and treatment methods is imperative. (−)-Epigallocatechin-3-O-gallate (EGCG), one of the major catechins in green tea, exerts an antifibrotic effect, although its mechanism remains unclear. Recently, it has been reported that microRNAs (miRNAs or miRs) transported by extracellular vesicles (EVs) from vascular endothelial cells (VECs) are involved in PF. In the present study, the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…EGCG also attenuated lysyl oxidase expression, an enzyme involved in cross-linking of ECM proteins collagen and fibronectin. Studies with TGF-β-treated human umbilical vein endothelial cells (HUVEC), and miRNA microarray analysis indicated that EGCG enhanced the expression of miR-6757-3p in extracellular vesicles from these cells [ 83 ]. Treatment of human lung fibroblasts with extracellular vesicles derived from EGCG-treated HUVECs downregulated the expression of TGF-β receptor 1, as well as the levels of fibrosis-related genes, including fibronectin and α-SMA [ 83 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%
“…EGCG also attenuated lysyl oxidase expression, an enzyme involved in cross-linking of ECM proteins collagen and fibronectin. Studies with TGF-β-treated human umbilical vein endothelial cells (HUVEC), and miRNA microarray analysis indicated that EGCG enhanced the expression of miR-6757-3p in extracellular vesicles from these cells [ 83 ]. Treatment of human lung fibroblasts with extracellular vesicles derived from EGCG-treated HUVECs downregulated the expression of TGF-β receptor 1, as well as the levels of fibrosis-related genes, including fibronectin and α-SMA [ 83 ].…”
Section: Major Plant-derived Compounds That Modulate Fibrosismentioning
confidence: 99%